Laboratory tests of the pull-out behaviour of spiral shaped steel fibres from concrete matrix - Hao, Yifei; Hao, Hong (2017)
© 2017 Taylor & Francis Group, London. The addition of short discrete steel fibres to increase strain capacity, impact resistance, energy absorption and toughness of concrete material has been widely studied and become a commonly accepted alternate form of reinforcement. It has been proven that the addition of fibres significantly increases the postpeak load bearing capacity of concrete in a hardened state. In recent years, intensive laboratory tests involving spiral shaped Steel Fibre Reinforced Concrete (SFRC) cylinder specimens and beams have indicated the superiority of fibres’ spiral geometry in terms of bonding of fibres in concrete matrix, leading to increased ductility as compared to other fibre types. Most bond-slip investigations have been focused primarily on straight or 2D fibres with little deformation capability. This study experimentally investigates the pull-out behaviour of spiral-shaped steel fibres from concrete matrix with various geometric parameters and pull-out rates. The compressive strength of concrete matrix was 44 MPa. The spiral fibres varying in coil diameter, pitch length and embedment length were pulled out using hydraulic machine. Quasi-static tests with pull-out velocity of 0.025 mm/s and dynamic tests with pull-out velocity of 0.25 mm/s and 0.5 mm/s were conducted to investigate the influence of loading rate. The results showed that several peak forces occurred before a final maximum pull-out force was recorded. The influences of coil diameter, pitch length, embedment length and pull-out velocity on the pull-out behaviour of spiral fibres from concrete matrix were investigated.